Comparison of detoxification capacity between broodstock and hybrid offspring in the gills of juvenile shrimp (Macrobrachium nipponense): Response to chronic ammonia stress. (20th June 2022) - Li, Yiming; Xu, Wenyue; Zhu, Bihong; Jiang, Qichen; Ye, Yucong; Zhao, Yunlong
Abstract: Ammonia nitrogen is an important source of water pollution that severely limits the development of aquaculture. Macrobrachium nipponense is widely cultivated due to its delicious meat, strong reproductive ability and short reproductive cycle, but the problems caused by germplasm degradation are becoming increasingly concerning. Hybridization is an efficient means to solve this problem. In this study, the parental population, Dianshan Lake (DS) and the hybrid population, DS ♀ × CD (Changjiang, CJ ♂ × Dongting, DT ♀ [SCD]) were exposed to 0, 1 or 10 mg/L total ammonia nitrogen (TAN) for 28 days. Our results indicated that the number of gill‐positive cells and the apoptosis rate of the two groups showed an upward trend with the ammonia nitrogen concentration increased. The ammonia metabolism‐related substance levels and the detoxifying enzyme activities in the gills of shrimp in the SCD group exposed to 10 mg/L of TAN were significantly higher than shrimp in the DS group ( p  < 0.05). As the TAN concentration increased, the respiratory‐related genes displayed a downward trend and the nitrogen metabolism‐related genes presented an upward trend. Our results suggest that the SCD population had a stronger detoxifying capacity and a greater stress resistance ability than the DS population when subjected to the same concentration of ammonia nitrogen stress.